ZnO and cobalt decorated ZnO NPs: Synthesis, photocatalysis and antimicrobial applications. (February 2023) - Singh, Karanpal; Nancy,; Kaur, Harpreet; Sharma, Pushpender Kumar; Singh, Gurjinder; Singh, Jagpreet
Abstract: The rapid growth of pollutants, both biological and non-biological, puts environmental systems in jeopardy. In view of this, the current study demonstrates the synthesis of undoped and Cobalt-doped zinc oxide nanoparticles (Co doped ZnO NPs) via co-precipitation method. The confirmation of incorporation of the Co dopant into ZnO NPs was verified through various spectroscopic and microscopic techniques. UV-absorption spectra of cobalt-doped ZnO NPs revealed a red shift with change of absorption spectra from 356 nm to 377 nm as compared to undoped ZnO NPs. XRD studies inferred that the average crystallite size of 0.5% and 1% Co-doped ZnO powder was obtained to be ∼16 nm and 14 nm respectively. A drop in band gap value from 3.48 eV to 3.30 eV provided as substantive evidence of the successful integration of Co 2+ ions inside the ZnO matrix. FESEM and HRTEM studies revealed that the obtained ZnO NPs are in narrow size distribution (15–20 nm) with a wurtzite crystal structure. The synthesized ZnO and Co–ZnO NPs showed excellent photocatalytic and antimicrobial potency towards reactive brown dye (RB-1) and two bacterial strains, respectively. 1% Co-doped ZnO demonstrated the maximum photocatalytic activity (∼95%), in contrast to 0.5% Co-doped ZnO and undoped ZnO. Thus, the findings of this work support the developed system has a dual role as the photocatalyst, and antibacterial agent for efficient environmental remediation. Graphical abstract: Image 1 Highlights: Bare and cobalt decorated ZnO NPs were prepared via simple co-precipitation method. Integration of Co 2+ ions in the ZnO matrix was verified via decrease in band. Microscopic studies confirmed the wurtzite crystal structure of ZnO NPs (15–20 nm). Co doped ZnO NPs showed enhanced photocatalysis and antibacterial potency.